A numerical model for ice crushing on concave surfaces. (15th September 2015) - Kim, Hyunwook; Daley, Claude; Colbourne, Bruce
Abstract: Laboratory scale cone-shaped ice compressive tests were performed, and a corresponding numerical simulation model using LS-DYNA ® was conducted. The numerical ice material model was based on a crushable foam model (MAT 63) with modified material properties applied. To simulate the saw tooth load–displacement pattern, which is commonly observed in experiments in ice, an additional function of 'maximum principal stress' failure criteria was added. The results of the experimental and numerical simulation were compared. The proposed numerical simulation model was extended to a 25 cm diameter cone-shaped ice specimen and a number of concave-shaped indenter cases were validated. Highlights: A numerical model for compressive cone-shaped ice tests was developed using LS-DYNA ® . A crushable foam with failure criteria was adopted to simulate a spalling event. Evaluation of scalability up to 2.5 times larger size was performed. The numerical model was verified from the viewpoint of global load and local load.